2003
DOI: 10.1002/etc.5620220209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating reptile exposure to cholinesterase‐inhibiting agrochemicals by serum butyrylcholinesterase activity

Abstract: Blood samples from lizards (Gallotia galloti) collected from two agricultural areas (Las Galletas and Punta del Hidalgo) and two reference areas on the Island of Tenerife (Canary Islands, Spain) were analyzed for butyrylcholinesterase (BChE) activity. Serum BChE activity was characterized first by in vitro experiments using selective substrates and inhibitors. Of the total cholinesterase (ChE) activity, 74% could be attributed to BChE activity. This portion of the total ChE activity was inhibited dose dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These authors reported that serum BChE activity of herpetofauna previously inhibited by OP did not recover totally in the presence of 2-PAM. Likewise, Sánchez-Hernández (2003) and Sánchez-Hernández et al (2004) observed similar increments of BChE activity reactivation after exposure to pesticides in Gallotia galloti (between 8 and 60%) and G. galloti palmae (between 5 and 53%) from agroecosystems. Accordingly, Parsons et al (2000) and Iko et al (2003) indicated that chemical reactivation of plasma phosphorylated ChE activity has been used for complementary diagnosis of OP intoxication.…”
Section: Discussionmentioning
confidence: 60%
“…These authors reported that serum BChE activity of herpetofauna previously inhibited by OP did not recover totally in the presence of 2-PAM. Likewise, Sánchez-Hernández (2003) and Sánchez-Hernández et al (2004) observed similar increments of BChE activity reactivation after exposure to pesticides in Gallotia galloti (between 8 and 60%) and G. galloti palmae (between 5 and 53%) from agroecosystems. Accordingly, Parsons et al (2000) and Iko et al (2003) indicated that chemical reactivation of plasma phosphorylated ChE activity has been used for complementary diagnosis of OP intoxication.…”
Section: Discussionmentioning
confidence: 60%
“…This was corroborated by the 2-PAM reactivation assay, which enabled us to identify organophosphates (OPs) as the agrochemicals responsible for plasma BChE depression in the animals collected from the agricultural sites; this suggestion do not, however, rule out the possibility that carbamates (CBs) also were involved. Chemical reactivation of plasma phosphorylated ChE activity has been used for complementary diagnosis of OP intoxication in birds (Parson et al 2000;Iko et al 2003) and reptiles (Sánchez-Hernández, 2003;Sánchez-Hernández et al 2004) (Table 1). Our data show that OP pesticides are an important class of pesticide to amphibians in rice fields.…”
Section: Discussionmentioning
confidence: 99%
“…BChE, mainly present in plasma, generally hydrolyzes butyrylthiocholine (BTC) at a higher rate than ATC and is not inhibited by excess substrate. AChE and BChE activities in blood are considered biomarkers of organophosphate (OP) pesticide or nerve agent exposure, because these agents inhibit both cholinesterases (ChEs; Coye et al ., ; Lotti, ; Sanchez‐Hernandez, ; Wilson et al ., ). Therefore, exposure to OP nerve agents and pesticides is normally assessed by measuring ChE activity in blood, and hence there is an urgent need for a simple, rapid, reliable and reproducible method for the accurate determination of both AChE and BChE activities in whole blood.…”
Section: Introductionmentioning
confidence: 99%